2006
DOI: 10.1016/j.bbrc.2006.10.102
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2-dependent protection from LPS induced inflammatory response and mortality by CDDO-Imidazolide

Abstract: Sepsis induced lethality is characterized by amplified host innate immune response. Nrf2, a bZIP transcription factor, regulates a battery of cellular antioxidative genes and maintains cellular redox homeostasis. This study demonstrates that increasing Nrf2 activity by a potent small molecule activator, CDDO-Im (1-[2-cyano-3-,12-dioxooleana-1,9(11)-dien-28-oyl]imidazole), protects from deregulation of lipopolysaccharide (LPS) induced innate immune response. In response to LPS stimuli, nrf2-deficient (nrf2 -/-)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
278
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 325 publications
(291 citation statements)
references
References 22 publications
10
278
3
Order By: Relevance
“…The reciprocal regulation between Nrf2 system function and PTEN expression has been suggested by several studies [34,40] . In this study, by using an Nrf2 inhibitor, we found that Nrf2 is causally involved in the effect of metformin on the regulation of PTEN and insulin signaling (Supplementary Figure 3).…”
Section: Discussionmentioning
confidence: 90%
“…The reciprocal regulation between Nrf2 system function and PTEN expression has been suggested by several studies [34,40] . In this study, by using an Nrf2 inhibitor, we found that Nrf2 is causally involved in the effect of metformin on the regulation of PTEN and insulin signaling (Supplementary Figure 3).…”
Section: Discussionmentioning
confidence: 90%
“…This Nrf2-mediated transcriptional interference appears to be independent of the level of reactive oxygen species. Although the conventional hypothesis is that Nrf2 alleviates inflammation as a secondary consequence of its antireactive oxygen species and anti-oxidation function (25), these results suggest that Nrf2 inhibits the induction of pro-inflammatory cytokine gene transcription. Thus, Nrf2 appears to be the key regulator of two important cytoprotective pathways, anti-inflammation and anti-oxidation.…”
Section: Anti-inflammation By Nrf2mentioning
confidence: 84%
“…In vivo, DMF treatment of experimental autoimmune encephalomyelitis (EAE) was also associated with a Th2 bias, which may be a consequence of induction of antigen-presenting antiinflammatory type II dendritic cells (DCs) (11). Consistent with these observations, results indicate Nrf2 itself may regulate innate and adaptive T-cell immune responses in models of organ-specific inflammation (12,13), including EAE (14,15). Nevertheless, although DMF demonstrated prominent reduction of inflammatory measures of MS (8,9), it is not clear that this benefit is mediated through activation of Nrf2.…”
mentioning
confidence: 77%